Improving Students’ Productive Disposition through Realistic Mathematics Education with Outdoor Approach - Saleh Haji; Yumiati Yumiati; Zamzaili Zamzaili (Department of Mathematics Education, Universitas Muhammadiyah Surakarta, 2019)
This study aimed to improve the students’ productive disposition (PD) through Realistic Mathematics Education (RME) learning with an outdoor approach based on school level. Productive disposition development is intended so that students can appreciate mathematics as a science needed for their lives. The method used in this research was a quasi-experimental study. The population was 210 students of the fifth grade of Elementary School from five schools. The sample was 75 fifth grade students. The data were collected by using a questionnaire. Data were analyzed using t-test to find out the difference between the experimental and the control group. The results of this study indicate that RME learning with the outdoor approach more influential than the conventional learning in improving PD in high school level. Otherwise, in medium and low level school, the conventional learning was more influential than the RME learning with the outdoor approach to improve the students’ PD. Therefore, it can be concluded that the school level needs to be considered in improving students’ productive disposition through RME learning with an outdoor approach. Moreover, RME learning with an outdoor approach as an alternative model to improve productive disposition of students.